Effectiveness of 23-valent pneumococcal polysaccharide vaccine on elderly long-term cancer survivors: a population-based propensity score matched cohort study. Issue 5 (16th May 2018) - Chiou, Wen-Yen; Lee, Moon-Sing; Hung, Shih-Kai; Lin, Hon-Yi; Lo, Yuan-Chen; Hsu, Feng-Chun; Tsai, Shiang-Jiun; Li, Chung-Yi
Abstract : Objective: The Advisory Committee on Immunization Practices in 2012 recommended the 23-valent pneumococcal polysaccharide vaccine (PPSV23) for adults with high risk of pneumonia. However, its effectiveness in cancer survivors has not been investigated. Our aim was to investigate the effectiveness of PPSV23 in these patients. Design: Population-based matched cohort study. Setting: Claim data were obtained from 1 million people registered with the National Health Insurance Research Database in 1996, and followed to 2010. People aged ≥75 years are eligible for receiving PPSV23 vaccination in Taiwan since 2007. Participants: Among the 30 249 patients with cancer, 6784 patients were 75 years or older eligible for PPSV23 vaccination. Among them, 1887 survived 5 or more years (ie, cancer survivors) after cancer diagnosis. We identified 377 cancer survivors who received PPSV23. A total of 754 propensity score matched unvaccinated patients were randomly selected. Intervention: PPSV23 vaccination. Primary outcome measures: The primary outcome was pneumonia hospitalisation. Potential confounders include influenza vaccination, vaccination period, cancer treatment modalities, comorbidities and sociodemographic variables. Results: After 2 years of follow-up, vaccinated patients had a significantly lower incidence rate of pneumonia hospitalisation at 73.66 per 1000 person-years (PYs), compared with 117.82 per 1000 PYs for unvaccinated patients. Additionally, the prevalence for pneumonia hospitalisation frequency of >0–1, >1–2, >2–3 and >3 times per PY was all consistently lower in the vaccinated group (6.63% vs 9.28%, 1.86% vs 2.52%, 0.80% vs 1.59% and 0.27% vs 0.53%, respectively). After adjustment for covariates, PPSV23 vaccine was significantly associated with reduced pneumonia hospitalisation risk, with an adjusted incidence rate ratio of 0.695 (p=0.030). While the cumulative pneumonia incidence was also significantly lower in the vaccinated patients (p=0.027), the overall survival time was similar (p=0.136). Conclusions: PPSV23 vaccination was associated with a significantly reduced rate of pneumonia hospitalisation in long-term cancer survivors.